Sosialisasi Prosedur Rencana Tindak Darurat dan Partisipasi Masyarakat dalam Pengelolaan Bendungan Wadaslintang - Aan Andriawan; Dwi Retno Astutik; Muhammad Ramadhani Suryolaksono (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Wadaslintang Dam is a strategic infrastructure in Wonosobo and Kebumen Regencies, Central Java, carrying a high downstream hazard risk if a structural failure occurs. This condition demands enhanced community preparedness through Emergency Action Plan socializations and stronger active participation in area management. This community service activity aims to improve the understanding and involvement of residents around the dam and catchment area to support sustainable management. Implementation methods included surveys, observations, socializations, mentoring, monitoring, and evaluation. Face-to-face sessions provided in-depth understanding of emergency procedures and the importance of disaster risk reduction. Program effectiveness was measured using pre-test and post-test instruments. Evaluation results recorded a significant surge in understanding, shown by an average score increase from 63.33 to 85.33. This proves face-to-face methods effectively foster two-way communication and interactive discussions, successfully strengthening community capacity to respond to emergencies while preserving the environment.